Inkling - Oppel, Kenneth, 1967- (Alfred A. Knopf, 2018)
When an inkblot, who can write, listen, learn, and draw, jumps out of Mr. Rylance's sketchbook, Ethan believes he may be the answer to their problems and names him Inkling.